Voices of Islam in Europe and Southeast Asia (American Journal of Islam and Society, 2006)
This workshop, co-organized by the Regional Studies Program, WalailakUniversity, Thailand, and the Department of Cross-cultural and RegionalStudies, University of Copenhagen, Denmark, and conceived of early in2005, took place a little over a week before the eruption of the “cartoon controversy,”which brought the issue of the relationship between Europe and theso-called “Muslim world” to the fore as never before. From January 20-22,2006, a group of almost thirty Muslim and non-Muslim specialists workingin Islamic studies and on the study of Muslim societies from fifteen countriesin Europe and Southeast Asia gathered in Nakhon Sri Thammarat, Thailand,to discuss the diverse “Voices of Islam” in these two regions. The workshopwas held in southern Thailand, where, in the ethnic Malay-majority borderprovinces, a violent insurgency over the last two years has claimed over 1,000lives and has heightened tensions between the local Muslim population andthe Thai state. Some observers have explained the intensification of the conflictas being due to the infiltration of foreign Islamist militants and the influenceof extremist Islamic discourses of struggle.The workshop focused on two major themes: how events following theSeptember 11 attacks have affected the nature of Islamic studies in Europeand Southeast Asia, and how changes in Islamic studies are impacting uponMuslims and their understanding of Islam in these two regions. While theworkshop presentations were given mainly in English (with a small numberof papers presented in Thai and Malay), a simultaneous interpreting servicewas available for local Thai Muslim (as well as non-Muslim) participants,who attended the workshop in significant numbers.A wide variety of papers were presented. However, if one theme couldsummarize the tone of the three days, it is that 9/11 has engendered a changingparadigm in these regions’ Islamic studies programs, even though manyof the changes may already have been underway prior to the attacks. In thecase of Southeast Asia, governments and the media in the region have attributedthe Muslim extremists’ ideology, at least partly, to the influence of ...